POLITIK DAN KEBIJAKAN: PENDIDIKAN AGAMA DAN KEAGAMAAN DI INDONESIA (Analisis Kebijakan PP No 55 Tahun 2007) - Rachmad Sobri (Edukasi Islami: Jurnal Pendidikan Islam, 2019)
AbstractThe article discusses about politics and religious education policy. This condition is motivated by the state’s mandate of education. One of which is contained the law number 20/2003 about Indonesian national education system for every citizen. One of the provisions oe the education system bring goodness to religious education has received less attention from the govermment. Such as boarding school institutions and madrasah educational institutions with the existence of government regulations number 55/2007 about religious education equated with formal education. Religious education institutions get financial aid and educational facilities. Then how religious education in the future with this new education system, where the direction of indonesian religious education in the future. Therefore this article focuses on the religious education system.Keywords: religious and religious education. AbstrakArtikel ini membahas tentang politik dan kebijakan pendidikan agama dan keagamaan. Kondisi ini dilatarbelakangi oleh adanya amanat konstitusi negara terhadap pendidikan. Salah satunya yang terdapat dalam Undang-Undang nomor 20/2003 tentang sistem pendidikan nasional di indonesia bagi setiap warga. Salah satu ketentuan dari sistem pendidikan tersebut membawa kebaikan bagi pendidikan agama dan keagmaan yang selama ini kurang mendapat perhatian dari pemerintah. Seperti lembaga pondok pesantren dan lembaga pendidikan madrasah dengan adanya Peraturan Pemerintah Nomor 55/2007 tentang pendidikan agama dan keagaaman disetarakan dengan pendidikan formal pada umumnya sehingga lembaga pendidikan agama mendapatkan bantuan keuangan dan fasilitas pendidikan. Lalu bagamana pendidikan agama kedepan dengan adanya sistem pendidikan yang baru ini, kemana arah pednididkan agama di indonesia kedepannya. Maka dari itu artikel ini memfokuskan pada sistem pendidikan agama dan keagamaan.